Priorities of Smartphone Online Shopping Applications for Young People - Takashi Okamoto; Jiro Yatsuhashi; Naoki Mizutani (International Telecommunications Society (ITS), 2017)
With widespread use of smartphones, many people use smartphone online shopping applications to enjoy online purchasing. However, Japanese young people's behavior and perceptions with regard to smartphone online shopping applications are unclear. To reveal these perceptions and priorities, this study examined Japanese respondents' adoption of online shopping applications on smartphones by applying a choice-based conjoint analysis. This study revealed that our respondents place the highest priority on the security considerations of online shopping applications. Popularity is another important attribute of online shopping applications. Gender, living area, and users' online purchase experience affect young people's priorities for smartphone online purchasing.
Keywords: 330; Online Shopping Behavior; Smartphone Shopping Applications; Priorities; Conjoint Analysis